Improved GMR characteristics of specular spin valves by nano-oxide layer formation with mixed gases - Jang, SH; Kang, T; Kim, HJ; Kim, KY (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2002)
A key requirement for spin valves (SV) with nano-oxide layers (NOL) are the formation of the smooth and uniform interface between NOL and magnetic layer for specular electron scattering. We investigated the natural oxidation conditions using mixed gases (O-2/N-2 and O-2/Ar) for the uniform NOL formation in specular SVs. We have compared the magnetoresistance (MR) properties and thermal stability of SVs with NOL formed in mixed gases with those formed using pure O-2. We can optimize oxidation conditions using mixed gases for enhanced MR ratio and reduced interlayer coupling field.
Keywords: MAGNETORESISTANCE; ENHANCEMENT